ANALYSE FACTORIELLE DES INHIBITIONS A LA PARITE HOMME-FEMME DANS LES MEDIAS AUDIOVISUELS DE KISANGANI - Damas ESOLE KESOLE KAYA (IJRDO - Journal of Social Science and Humanities Research, 2019)
Gender parity in all areas of life is currently considered an antidote to the different gender-related inequalities seen throughout the world since time immemorial. The existence of several international, regional and national legal instruments testifies to this concern to create a world where men and women are called to play the same role, not only for the development of their social environment, but also for their own fulfillment. This eventually pushed the Congolese legislator to vote on the law n ° 15/013 of August 1st, 2015 on the modalities of application of the rights of the woman and the parity. However, it is clear that, despite this formal desire, we are far from achieving significant progress on the ground. The area particular Kisangani media is among those who suffer from it. This study first aims to identify the various factors that slow down this state of affairs and then raise the awareness of the different parties (public authorities, managers as well as men and women in the media) about the need for them. Extirpate. It shows that these inhibitory factors result from public authorities and media professionals (managers, men and women). The antidote lies, among other things, in the establishment of gender-sensitive media management (GMSG).